PELATIHAN SMART INVENTORY DAN PEMESANAN ONLINE UNTUK PELAKU USAHA KEDAI KOPI BERBASIS IoT DI FOOD COURT UNILAM TAHUN 2024 - Yulikuspartono; Zulkifli; Ela Herawati, (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
This Community Service Program (PKM) aimed to improve the operational efficiency of coffee shop entrepreneurs at the UNILAM Food Court through training on the use of Smart Inventory and online ordering systems based on the Internet of Things (IoT). The main problems faced by business partners include inefficient inventory management, manual ordering processes, and long queues that reduce service quality. During the training, participants were introduced to the basics of IoT, technical components of smart inventory systems, and the integration of digital ordering to minimize waste and improve data accuracy. The results show high enthusiasm among the participants and an emerging understanding of the importance of digitalization to increase business competitiveness. This training provided foundational knowledge and practical skills in implementing simple technology solutions, while also reinforcing the implementation of the Tri Dharma of Higher Education in supporting a more modern and efficient campus-based MSME ecosystem.